Persepsi Guru-Siswa Terhadap AI Dalam Pembelajaran Teknik Mesin Di SMKN 3 Singaraja: Teacher-Student Perceptions Of Ai In Mechanical Engineering Learning At SMKN 3 Singaraja - Bayazid Al Bustami; Nyoman Pasek Nugraha; Edi Elisa; Kadek Rihendra Dantes; Gede Widayana (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze teachers’ and students’ perceptions of the use of Artificial Intelligence (AI) in learning within the Mechanical Engineering Department at SMKN 3 Singaraja. The study is motivated by the increasing integration of AI technology in vocational education, which requires readiness from both teachers and students. This research employs a qualitative exploratory approach. Participants were selected using purposive sampling, consisting of teachers and students of the Mechanical Engineering Department. Data were collected through semi-structured interviews, non-participant observation, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that teachers perceive AI as an effective learning aid that supports theoretical instruction and administrative tasks, but it cannot replace hands-on practical training in workshops. Meanwhile, students view AI as a learning assistant that helps them understand materials and solve technical problems, although it may lead to dependency risks. In conclusion, AI functions as a supporting tool rather than a replacement for teachers. Proper regulations, improved digital literacy, and strengthened teacher roles are required for effective implementation in vocational education.